2017
DOI: 10.18632/oncotarget.21837
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase type 5 and cancers: progress and challenges

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 265 publications
(154 reference statements)
1
25
0
Order By: Relevance
“…Indeed, PDE10i's also inhibit growth of colorectal cancer cells (170,171); however, when both PDE5 and PDE10 are inhibited, anti-tumor efficacy is improved in preclinical models (24). Although enthusiasm for PDE5i's as chemopreventives is growing (172), it should be noted that PDE5i's similarly prevented prostate carcinogenesis in preclinical models but did not appear to reduce risk or recurrence in clinical studies (173). Perhaps even more concerning, PDE5A appears to suppress melanoma cell invasion in mice (174) yet a recent systematic review and meta-analysis showed that PDE5i's actually increase risk for melanoma and basal cell carcinoma in humans (175).…”
Section: (167 168)) Althoughmentioning
confidence: 99%
“…Indeed, PDE10i's also inhibit growth of colorectal cancer cells (170,171); however, when both PDE5 and PDE10 are inhibited, anti-tumor efficacy is improved in preclinical models (24). Although enthusiasm for PDE5i's as chemopreventives is growing (172), it should be noted that PDE5i's similarly prevented prostate carcinogenesis in preclinical models but did not appear to reduce risk or recurrence in clinical studies (173). Perhaps even more concerning, PDE5A appears to suppress melanoma cell invasion in mice (174) yet a recent systematic review and meta-analysis showed that PDE5i's actually increase risk for melanoma and basal cell carcinoma in humans (175).…”
Section: (167 168)) Althoughmentioning
confidence: 99%
“…In addition, according to recent findings, PDE5i has been shown to act as potential anti-cancer drugs on tumor cell lines, either for their chemosensitizing effects or as chemopreventive agents (Barone et al, 2015). Nevertheless, the majority of the reports rely on preclinical evidences making it difficult to draw clear conclusions and to provide appropriate clinical guidelines relating thereto (Barone et al, 2017). In addition, recent reports by us and other groups have identified a protective role of PDE5 expression in glioblastoma multiforme (GBM) and melanoma aggressiveness and a negative role of PDE5i treatment in the progression of metastatic melanoma (Li et al, 2014;Cesarini et al, 2017;Wang et al, 2017;Shkolyar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of PDE5 and the cGMP-signaling pathway turns out to be often altered in several human cancers, such as colon, breast, lung, and bladder carcinomas (Barone et al, 2015). However, the effective role of cGMP in tumorigenesis is still debated and, above all, it is heavily dependent upon the tumor type and the model system investigated (Barone et al, 2017). Benign prostatic hyperplasia (BPH) is a non-cancerous histologic change of the prostate gland often causing lower urinary tract symptoms (LUTS) when associated with benign prostatic enlargement (BPE).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of iNOS and ARG-1 also has key roles in MDSC activation. Phosphodiesterase-5 (PDE5) inhibitors includesildenafil, tadalafil, and vardenafil, they are emerged as a promising approach to inhibit proliferation, motility and invasion of certain cancer cells including glioma (126). These inhibitors are reported to suppress both iNOS and ARG-1 activities in MDSC, thereby decrease MDSC immunosuppressive functions (127,128).…”
Section: Inactivation Of Mdscsmentioning
confidence: 99%